2016
DOI: 10.1103/physreve.94.052149
|View full text |Cite
|
Sign up to set email alerts
|

Effect of long-range interactions on the phase transition of Axelrod's model

Abstract: Axelrod's model with F = 2 cultural features, where each feature can assume k states drawn from a Poisson distribution of parameter q, exhibits a continuous nonequilibrium phase transition in the square lattice. Here we use extensive Monte Carlo simulations and finite size scaling to study the critical behavior of the order parameter ρ, which is the fraction of sites that belong to the largest domain of an absorbing configuration averaged over many runs. We find that it vanishes as ρ ∼ q 0 c − q β with β ≈ 0.2… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…Once the dynamics reaches an absorbing configuration, we count the number of cultural domains (N d ) and record the size of the largest one (S d ), as usual [5][6][7][8][9]. In time, a cultural domain is defined as a connected subgraph where the agents have the same culture (i.e., they share all cultural features).…”
Section: Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Once the dynamics reaches an absorbing configuration, we count the number of cultural domains (N d ) and record the size of the largest one (S d ), as usual [5][6][7][8][9]. In time, a cultural domain is defined as a connected subgraph where the agents have the same culture (i.e., they share all cultural features).…”
Section: Modelmentioning
confidence: 99%
“…Somewhat surprisingly, in spite of this homogenizing mechanism, Axelrod's model exhibits global polarization (i.e., a stable multicultural regime) for large q in the case the agents are fixed to the sites of a square lattice and interact with their nearest neighbors only [4]. Variations of the original model have revealed that the relaxation of the homophilic interaction rules and the expansion of the interaction neighborhoods favor cultural homogenization (i.e., a stable monocultural regime) [5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…This concept has its motivations from studies of cultural dissemination, using for example the Axelrod's model [27,28]. The cultural domains have been used as the order parameter in the study of cultural dissemination [8,[29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…The transition was reported to be continuous for one-dimensional networks and discontinuous for two dimensions (2D) when F > 2 [4], although a continuous transition is recovered when the topology becomes small world [3]. On the other hand, for F = 2, the type of the transition is the opposite: continuous for 2D, and discontinuous for small-world networks [5]. The case of F = 2 is important due to the possibility of taking an analytical approach to study the model [6].…”
Section: Introductionmentioning
confidence: 99%
“…* spinto@df.uba.ar Several scaling relationships have been found in the Axelrod model. For instance, in [7] and [5] a finite-size scaling analysis is performed for F = 2 in square lattices and smallworld networks. A scaling relation between Q and size N can be found in scale-free networks for F = 10 [3], a scaling relationship between the density of active bonds and time in a one-dimensional network in [8], and the finding of an effective noise rate is explored in [9].…”
Section: Introductionmentioning
confidence: 99%